2015
DOI: 10.1093/bja/aev027
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitive cardiac troponin T measurements in prediction of non-cardiac complications after major abdominal surgery

Abstract: NCT02150486.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
1
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 27 publications
4
60
1
6
Order By: Relevance
“…These findings extend and corroborate previous work on PMI and efforts aimed at improving outcomes after noncardiac surgery 1,2,[4][5][6]19 The high incidence of PMI and the high mortality rate observed in this study suggest that the specific selection criteria used to identify high-risk patients deserve to be replicated in future studies. Ideally, these should include a randomized controlled trial testing the effect of active surveillance combined with an active response protocol on clinical and economic outcomes.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…These findings extend and corroborate previous work on PMI and efforts aimed at improving outcomes after noncardiac surgery 1,2,[4][5][6]19 The high incidence of PMI and the high mortality rate observed in this study suggest that the specific selection criteria used to identify high-risk patients deserve to be replicated in future studies. Ideally, these should include a randomized controlled trial testing the effect of active surveillance combined with an active response protocol on clinical and economic outcomes.…”
supporting
confidence: 90%
“…PMI is a common complication after noncardiac surgery and, despite early detection during routine clini- (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) 1261 (51) 18 1626 (64) 3 (1)(2)(3)(4)(5)(6)(7)(8) No PMI 12 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) 957 (46) 15 (10)(11)(12)(13)(14)(15)(16)(17)(...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…24 Noordzij et al suggested that a relative change in hs-cTnT >50% from baseline value seemed to be appropriate for diagnosis of myocardial injury. 21 Eggers et al tested the best cutoff value to diagnose acute myocardial infarction among changes in hs-cTnT ≥20%, ≥50%, or ≥100% from baseline. They found that a change >50% was associated with the most frequent false-negative results in diagnosing acute myocardial infarction.…”
Section: Incidence Of Composite Of In-hospital Cardiovascular Eventsmentioning
confidence: 99%